2021
DOI: 10.32322/jhsm.857780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hematologic indices in patients with thyrotoxicosis with distinct etiologies: a case-control study

Abstract: Aim: Thyrotoxicosis is a clinical state of inappropriately high levels of free T4 (thyroxine) and/or free T3 (tri-iodothyronine) in the body caused by distinct etiologies including Graves' disease (GD), subacute thyroiditis (SAT), toxic adenoma and toxic multinodular goiter (TMNG). Simple hematologic indices such as neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) and mean platelet volume (MPV) have increasingly been mentioned as measures of presence and severity of thyrotoxicosis. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the study of Çetin et al, NLR and PLR were found to be statistically significantly higher in SAT patients. However, no significant relationship was found between other thyrotoxicosis including GD [16]. In most of the studies, these ratios have been used in the differential diagnosis of thyrotoxicosis, and there is not enough study about the place of GD in the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Çetin et al, NLR and PLR were found to be statistically significantly higher in SAT patients. However, no significant relationship was found between other thyrotoxicosis including GD [16]. In most of the studies, these ratios have been used in the differential diagnosis of thyrotoxicosis, and there is not enough study about the place of GD in the prognosis.…”
Section: Discussionmentioning
confidence: 99%